Socialization Model of Tacit-Tacit Transfer Knowledge through Appreciative Inquiry Approach - Ani Wahyu Rachmawati (Research Synergy Foundation, 2017)
The aims of study is to describe combination of two big theory between Socialization model of tacit-tacit transfer knowledge and appreciative inquiry approach conceptually. This research idea comes to find better ways in tacit-tacit transfer of knowledge in knowledge management theory. This research is conceptual research and the limitation is about empirical study itself. The result of conceptual paper combine the process of tacit-tacit tansfer knowledge and appreciate inquiry in mental model, creative dialogue and develop mutual trust. Appreciative inquiry as a method to increase positive sense in tranfer knowlegde can be applied in tacit-tacit transfer knowledge phase in SECI Model.